Предмет: Алгебра,
автор: Iriska2008
Найдите значения выражения:
xy-3x-2y^2+6y при x=9.2; y=4,1
Ответы
Автор ответа:
1
xy - 3x - 2y^2 + 6y = x(y-3) -2y(y-3) = (y-3)(x-2y)
x = 9.2
y = 4.1
(4.1-3)(9.2-2*4.1) = 1.1 * (9.2 - 8.2) = 1.1*1 = 1.1
x = 9.2
y = 4.1
(4.1-3)(9.2-2*4.1) = 1.1 * (9.2 - 8.2) = 1.1*1 = 1.1
Похожие вопросы
Предмет: Математика,
автор: Help007228
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: klartin
Предмет: Русский язык,
автор: shodi2010
Предмет: Русский язык,
автор: 07585838384747